Manajemen risiko akad pembiayaan (mudharabah dan musyarakah) pada bank syariah indonesia (bsi) periode 2022-2024 menggunakan pendekatan value at risk (var) metode variance-covarian - Patrisia, Ammabel Eka (Maliki Interdisciplinary Journal, 2025)
The Indonesian sharia banking industry experienced significant growth in 2024, with total assets reaching Rp980.30 trillion and financing amounting to Rp643.55 trillion. However, risk management challenges persist, particularly with a gross Non-Performing Financing (NPF) ratio of 2.12% and a net NPF of 0.79%. Mudharabah and Musyarakah contracts inherently carry higher risks compared to Murabahah. This study analyzes the financing risk of Mudharabah and Musyarakah in Bank Syariah Indonesia (BSI) using the Value at Risk (VaR) approach with the Variance-Covariance method. Data from 2022–2024 reveal consistent growth in Musyarakah financing and sharp fluctuations followed by recovery in Mudharabah financing. Mudharabah returns are higher but more volatile, while Musyarakah returns are more stable. A negative covariance (-0.02%) between the returns indicates diversification benefits. The combined portfolio yields an average return of 2.28% with a standard deviation of 6.44%, signifying a substantial reduction in risk. The portfolio's VaR of Rp12,411,245 at a 95% confidence level reflects the maximum potential loss. This approach proves effective in quantitatively measuring risk and supporting the bank's compliance with sharia financing risk management regulations.